Providing professional development approaches for novice lecturers: a case of one Chinese university - Hong, Yu; Abdullah, Arnida; Muhamad, Mohd Mokhtar (Human Resources Management Academic Research Society (HRMARS), 2024)
In the higher education field, professional development helps novice lecturers transform their identities and familiarize themselves with their work to become more comfortable teaching at the university. The task of university management in the professional development of novice lecturers is to supervise their professional growth and to design and continuously improve professional development approaches aimed at enhancing their capabilities. The purpose of this qualitative case study is from the university management perspective to explore the various approaches employed by a particular university in fostering the professional development of novice lecturers and what the benefits of these approaches bring to novice lecturers. To achieve this, in-depth interviews were conducted with six members of the university management, and documentary data was also gathered. A thematic analysis was subsequently conducted to extract key themes from the collected data. This study revealed that in this selected university, the university management assists and supports the professional development of novice lecturers through a range of approaches such as workshops and lectures, teaching competitions, mentorship programs, and participation in university-enterprise collaborations. These diversified professional development approaches enable novice lecturers to enhance their professional skills and competencies, as well as self-confidence, laying a strong base for them to grow into outstanding educators. It is recommended that the university management maintain and improve existing professional development approaches and innovate other activities and programs to support novice lecturers on an ongoing basis.